Effect of human immunodeficiency virus on blood-brain barrier integrity and function: an update - Atluri, Venkata Subba Rao; Hidalgo, Melissa; Samikkannu, Thangavel; Kurapati, Kesava Rao Venkata; Jayant, Rahul Dev; Sagar, Vidya; Nair, Madhavan P. N. (Frontiers in Cellular Neuroscience, 2015)
The blood-brain barrier (BBB) is a diffusion barrier and has an important role in maintaining a precisely regulated microenvironment and protects the neural tissue from infectious agents and toxins in the circulating system. Compromised BBB integrity plays a major role in the pathogenesis of retroviral associated neurological diseases. Human Immunodeficiency Virus (HIV) infection in the Central Nervous System (CNS) is an early event even before the serodiagnosis for HIV positivity or the initiation of antiretroviral therapy (ART), resulting in neurological complications in many of the infected patients. Macrophages/microglia and astrocytes (in low levels) are the most productively/latently infected cell types within the CNS. In this brief review, we have discussed about the effect of HIV infection and viral proteins released on the integrity and function of BBB, which may contribute to the progression of HIV associated neurocognitive disorders.